2017
DOI: 10.14704/nq.2017.15.2.1030
|View full text |Cite
|
Sign up to set email alerts
|

Coding by Quantum Entanglement Entropy

Abstract: In our view, the Universe can be described as having two forms of energy: one related to attractive gravitational forces, which is negative, and the other related to mass according to Einstein's formula E = mc 2 , which is positive. The generation of nonequilibrium structures (such as Bénard vortices or chemical oscillations), where energy is conserved, also corresponds to a free lunch, for the price of nonequilibrium structures is entropy, and not energy. In this context, we can specify the origin of negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The World is coded by the Quantum Entanglement Entropy (QEE), so we think that this a "God's Code". The QEE means a selection, much more complex than Darwinian one, through the coding by Quantum Entanglement Entropy, leading to consciousness explained without the errors of over-simulations of the science ruling before the Quantum Physics Era [12]. Agriculture is today the main producer of the World Epidemic of Cancer !…”
Section: Resultsmentioning
confidence: 99%
“…The World is coded by the Quantum Entanglement Entropy (QEE), so we think that this a "God's Code". The QEE means a selection, much more complex than Darwinian one, through the coding by Quantum Entanglement Entropy, leading to consciousness explained without the errors of over-simulations of the science ruling before the Quantum Physics Era [12]. Agriculture is today the main producer of the World Epidemic of Cancer !…”
Section: Resultsmentioning
confidence: 99%
“…They also found that an unexplained drop in cholesterol levels one year before a cancer diagnosis increased the risk of cancer in both statin users and nonusers. This unexplained drop in cholesterol may be caused by distant coincidences of the non-linear deviation term (NDT) directed by the Quantum Entanglement Entropy (QEE) effects [3][4][5].…”
Section: Disentangling the Association Between Statins Cholesterol mentioning
confidence: 99%
“…Here we must as first formulate a new Main Natural Law: the Quantum Entanglement Entropy (QEE) [3]. Through above resonances the QEE is causing a metastasis of correlations, antagonistically intertwining all types of potentially conflicting interests [4,5].…”
Section: The Twofaced New Main Law Of Naturementioning
confidence: 99%
“…The World is coded by the Quantum Entanglement Entropy (QEE), so we think that this a "God's Code". The QEE means a selection, much more complex than Darwinian one, through the coding by Quantum Entanglement Entropy, leading to consciousness explained without the errors of over-simulations of the science ruling before the Quantum Physics Era [15].…”
Section: The Food Supply Through Agricultural Usementioning
confidence: 99%